The Effect of Enterprise Risk Management (ERM) Disclosure on Firm Value Mediated by Profitability: Empirical Study on Banks Listed on the IDX 2018-2020 - Kristiani, Yulia Iwan Andri; Hadiprajitno, Basuki (Universitas Proklamasi 45, 2023)
One important aspect of company value is ERM (Enterprise Risk Management). ERM can manage risks well so that company goals can be achieved. This study aims to see the effect of ERM disclosure on profitability, and the value of a company, as well as profitability on firm value. This study uses quantitative data with the panel data regression analysis method. Secondary data in the study comes from audited annual financial reports of financial companies in the form of banks, which have been listed on the IDX from 2018 to 2020, and can be downloaded from the bank's website. The data used is in 2018-2020 in annual form. The analysis technique in testing and proving the hypothesis used in the study is panel data regression analysis. The data is processed using the Eviews 12 application. The results showed that the variation in the following year's Company Value (Q Ratiot+1) can be explained by variations in the independent variables in the model, namely ERM Disclosure, ROA, Company Size, LDR, and Dividends the following year and the independent variables ERM Disclosure, ROA, Company Size, LDR, and Dividends the following year, together (simultaneously) affect the dependent variable Company Value the following year (Q Ratiot+1).